2020
DOI: 10.1111/lang.12411
|View full text |Cite
|
Sign up to set email alerts
|

Learning Vocabulary Through Listening: The Role of Vocabulary Knowledge and Listening Proficiency

Abstract: This study explored the impact of preexisting vocabulary knowledge (PVK) and listening proficiency on the vocabulary learning through listening of 137 Chinese learners of English, when provided with three types of oral vocabulary explanations—second language (L2), codeswitching (CS), and contrastive focus‐on‐form (CFoF)—and when no explanations (NE) were provided (extending Zhang & Graham, 2019). Listening proficiency was a more important factor influencing vocabulary learning through aural input than PVK was,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The Aural Lex (Milton & Hopkins, 2006) utilizes a spoken Yes/No format that does not require learners to demonstrate knowledge of the form-meaning link. The spoken receptive meaning recognition (multiple-choice) Listening Vocabulary Levels Test (LVLT) is only available for Japanese (McLean et al, 2015), Chinese (Zhang & Graham, 2020) and Vietnamese (Ha, 2021) learners, as tests that expect to measure spoken receptive meaning-recognition lexical knowledge should present answer options in the learners' L1 so as not to confound L2 written receptive and spoken receptive ability. However, while future research should strive to utilize appropriate tests, it is not always possible.…”
Section: Introductionmentioning
confidence: 99%
“…The Aural Lex (Milton & Hopkins, 2006) utilizes a spoken Yes/No format that does not require learners to demonstrate knowledge of the form-meaning link. The spoken receptive meaning recognition (multiple-choice) Listening Vocabulary Levels Test (LVLT) is only available for Japanese (McLean et al, 2015), Chinese (Zhang & Graham, 2020) and Vietnamese (Ha, 2021) learners, as tests that expect to measure spoken receptive meaning-recognition lexical knowledge should present answer options in the learners' L1 so as not to confound L2 written receptive and spoken receptive ability. However, while future research should strive to utilize appropriate tests, it is not always possible.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being in line with previous empirical research (Staehr, 2009), this result implies that for weaker listeners there are more dimensions influencing their listening performance. In other words, those language learners draw more often on other factors when interpreting spoken input (Zhang & Graham, 2020), which was already suggested in previous research studies (e.g., Bonk, 2000;van Zeeland & Schmitt, 2013b).…”
Section: -Contextualization Of Resultssupporting
confidence: 59%
“…A third factor that renders listening a comparatively more difficult skill is that listeners might need to pay attention to additional and complementary ways to deliver the message (Zhang & Graham, 2020). In listening comprehension, the context might be more important than in reading, as the speaker has other 'channels' to convey their message.…”
Section: Listening In Language Learningmentioning
confidence: 99%
“…Results showed higher early literacy scores in the experimental group after electronic book intervention than in the control group that used traditional book material. Several studies have also reported positive effects of digital storybooks on early literacy skills and language development (Shamir and Korat, 2007;Shamir and Shlafer, 2011;Shamir and Baruch, 2012;Neumann, 2014;Neumann and Neumann, 2017;Strouse and Ganea, 2017;Zipke, 2017;Herodotou, 2018;Lee, 2020). However, there is still a lack of research on how the specific conditions in digital reading impact children's understanding of stories and how shared reading interaction and adults' responsive strategies during digital reading are affected by the digital device (Herodotou, 2018;Courage, 2019).…”
Section: Digital Stories and Early Literacymentioning
confidence: 99%